Limiting Forms for Demand Functions: Tests of Some Specific Hypotheses - Ramsey, J. B. (The Review of Economics and Statistics, 1974)
IN Ramsey (1972) the author discussed the conditions under which limiting approximations to own price demand curves can be obtained. The objective to be pursued in this paper is to test with budget data some of the specific hypotheses generated in the previous paper. The results to be presented are to be regarded only as initial efforts. Their main function is to indicate whether the hypothesized models can meet some fairly weak tests and to indicate the nature of some of the practical problems to be faced in testing such hypotheses.